The Brazilian Payroll Lending Experiment - Christiano Arrigoni Coelho; Bruno Funchal; Jo\~ao Manoel Pinho de Mello (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2010)
In 2004, Brazil provided an interesting natural experiment concerning personal credit. A new law was enacted allowing banks to offer loans with repayment through automatic payroll or social security benefit deduction, thus removing a significant part of the moral hazard problem by eliminating the choice of default when debtors are able to pay their loans out of their wages. We estimate the impact of the new law using car loans as a control group. We find that, at the industry level, the new law has caused a reduction in interest rates and an increase in the volume of personal credit.
Keywords: G21; D01; C33; K00; E44; 330; Credit markets; collateral; difference-in-differences. JEL Code: G21; D01; C33; K00; E44.; Kredit; Private Verschuldung; Lohn; Kreditsicherung; Brasilien